The effects of radiation therapy on the macrophage response in cancer - Beach, Callum; MacLean, David; Majorova, Dominika; Arnold, James N.; Olcina, Monica M. (Frontiers in Oncology, 2022)
The efficacy of radiotherapy, a mainstay of cancer treatment, is strongly influenced by both cellular and non-cellular features of the tumor microenvironment (TME). Tumor-associated macrophages (TAMs) are a heterogeneous population within the TME and their prevalence significantly correlates with patient prognosis in a range of cancers. Macrophages display intrinsic radio-resistance and radiotherapy can influence TAM recruitment and phenotype. However, whether radiotherapy alone can effectively “reprogram” TAMs to display anti-tumor phenotypes appears conflicting. Here, we discuss the effect of radiation on macrophage recruitment and plasticity in cancer, while emphasizing the role of specific TME components which may compromise the tumor response to radiation and influence macrophage function. In particular, this review will focus on soluble factors (cytokines, chemokines and components of the complement system) as well as physical changes to the TME. Since the macrophage response has the potential to influence radiotherapy outcomes this population may represent a drug target for improving treatment. An enhanced understanding of components of the TME impacting radiation-induced TAM recruitment and function may help consider the scope for future therapeutic avenues to target this plastic and pervasive population.